산업안전보건법상 석면관리 체계의 문제점에 대한 소고 - 조흠학; 박민수 (원광법학, 38(1), 2022)
본 연구는 산업현장에서 가장 기본이 되는 산업안전보건법상의 석면 관련 법령과 석면안전관리법 간의 관계를 명확하게 규정하기 위해, 사업장 내에서 석면의 사용주체와 관리주체의 문제점을 파악하여 정부 관계부처간의 책임 범위를 명확하게 제시하는 것을 목적으로 한다. 이를 위해 현행 산업안전보건법 상 석면관리제도의 문제점 중의 하나인 석면 사용주체의 불명확성 (산업안전보건법 제117조제1항의 “누구든지”) 및 석면 관리 체계의 문제점인 산업안전보건법 상의 석면함유가능물질의 범위 및 산업안전보건법 상의 석면회수조치의 필요성에 대해 연구를 진행하였다. 연구 결과, 첫째, 산업안전보건법은 사업주의 의무로 규정되어 있고 사업주는 산업재해로부터 근로자를 보호하기 위해 안전보건조치를 수행해야한다. 현행 산업안전보건법 제117조 제1항의 석면의 사용주체도 사업주로 되어있어야 하지만 현재 “누구든지”로 표현되어 있다. 그러나 이러한 표현은 산업안전보건법의 목적에 어긋나고, 석면 취급 근로자의 보호 규정 주체가 사업주이므로 산업안전보건법 제117조 제1항의 “누구든지”를 “사업주”로 개정하는 것이 석면의 사용주체를 명확하게 할 것이라 판단된다. 둘째, 현행 석면함유가능물질에 관한 법적 근거는 산업안전보건법상에 없고 석면안전관리법 상에 그 근거 조문이 있다. 특히 현행 석면안전관리법에서 석면함유가능물질을 4가지 광물만으로 규정하고 있어, 4가지 광물 이외의 석면함유가능물질에 관한 관리의 문제가 발생할 수 있다. 또한 석면함유가능물질에 대한 관리도 석면안전관리법에 근거하여 이루어지고 있다. 따라서 석면함유가능물질의 관리에 대한 법적 근거가 없는 산업안전보건법이 아니라 석면안전관리법에 관리하는 것이 타당하다고 판단된다. 셋째, 현행 산업안전보건법 제117조 제3항에서는 고용노동부장관의 승인요건에 적합하지 않은 경우에는 승인을 취소할 수 있도록 규정하고 있으나, 승인이 취소된 석면 관련 제품에 대해 고용노동부장관이 회수를 명할 수 있는 법적 근거 조항이 산업안전보건법상에 없다. 따라서 산업안전보건법 제117조의 제5항에 “고용노동부장관은 제3항에 의해 승인이 취소된 경우에는 지체 없이 유통 중인 석면의 회수에 필요한 조치를 명할 수 있다.”는 조항을 추가할 필요가 있을 것으로 판단된다. 마지막으로 본 연구 결과를 토대로 산업안전보건법에 반영하면 산업안전보건법상의 석면의 사용주체, 석면함유가능물질의 관리 범위 및 석면 회수조치에 대한 두 행정집행 기관의 행정집행 상의 혼란을 방지시킬 수 있을 것으로 사료된다. 또한 사업장에서 석면 관련 사고의 책임을 분명하게 밝힐 수 있을 것으로 기대한다. To clarify the asbestos management between the Occupational Safety and Health Act and the Asbestos Safety Control Act, this study aims is to examine the expression of asbestos users in the Occupational Safety and Health Act and the scope of responsibility between government-related ministries on asbestos management was reviewed. To identify the problems of the current asbestos management in the OSHA Act, this study reviewed three perspectives such as examining the problem of uncertainty of asbestos users due to the expression of “no person” in OSHA Act Article 117, reviewing the scope of the asbestos-containing products in the OSHA Act and considering the necessity of the recall of asbestos in the OSHA Act. Results of this study were summarized as follow, firstly, we think that the subject of asbestos users should be changed in accordance with the purpose of the OSHA Act. The OSHA Act is stipulated as duties of business owners and the business owners must carry out safety and health measures to protect workers from industrial accidents. The subject of asbestos users in the OSHA Act Article 117 should be a business owner, but it is now expressed as “No person”. But that would defeat the purpose of the OSHA Act, the business owners are the subject of protection of asbestos handling workers. Therefore, it is considered reasonable to revise “No person” in the OSHA Act Article 117 to “business owner”. Secondly, the definition of the current asbestos-containing material has no legal basis in OSHA Act, but there is a legal basis for the asbestos safety management law. In particular, the current Asbestos Safety Management Act stipulates asbestos-containing material as only four materials, which may cause problems in the management of asbestos-containing material other than four materials. In addition, management of asbestos-containing material is also carried out based on the Asbestos Safety Management Act. Therefore, it is considered reasonable to manage asbestos-containing materials under the Asbestos Safety Management Act, not the OSHA Act, which does not have a legal basis for the management of asbestos-containing materials. Finally, the OSHA Act Article 117(2) presents that the use of asbestos can be used if the Minister of Employment and Labor is approved, the OSHA Act Article 117(3) stipulates that approval can be revoked if it is not in conformity with the requirements for approval of the Minister of Employment and Labor. However, if the approval is revoked, there is no legal basis for the Minister of Employment and Labor to order the recall of the canceled product. Therefore, a new provision must be established for the Minister of Employment and Labor to order the recall of the canceled product whose approval has been revoked. Based on these results, this study clearly suggested the subject of asbestos users and the subject of asbestos management in accordance with the purpose of the OSHA Act. We think that it is possible to prevent confusion in industrial sites by interpreting asbestos-related laws under the OSHA Act. KCI Citation Count: 0